STUDENTS’ WAYS OF UNDERSTANDING AND THINKING BASED ON HAREL’S THEORY IN SOLVING SET PROBLEMS - Samosir, Christina Monika; Herman, Tatang (Universitas Pelita Harapan, 2023)
Ways of thinking (WoT) and Ways of Understanding (WoU) are important in learning mathematics. This study aims to analyze the characteristics of students' ways of thinking (WoT) and ways of understanding (WoU) when solving set problems. The participants in this study were 27 students in the seventh grade at a private secondary school in Bandung. Four students were selected as research subjects. The research method used is qualitative research. The instruments in this study were the researchers and the set material problem-solving test. The data collection technique in this study was carried out through a test, interviews, and documentation. The research results showed that the majority of students who were correct in their way of thinking were also correct in their way of understanding. And the majority of students who have the incorrect way of thinking also have the incorrect way of understanding. The study's results also indicated that the majority of student errors stemmed from a lack of proper understanding of the question and the concept of set theory.BAHASA INDONESIA ABSTRACT: Cara berpikir dan cara memahami merupakan hal yang penting dalam belajar matematika. Penelitian ini bertujuan untuk menganalisis karakteristik cara berpikir dan cara memahami siswa dalam menyelesaikan masalah himpunan. Partisipan pada penelitian ini adalah siswa kelas VII di salah satu SMP Swasta di Bandung berjumlah 27 partisipan. Empat siswa dipilih sebagai subjek penelitian. Metode penelitian yang digunakan adalah penelitian kualitatif. Instrumen dalam penelitian ini adalah peneliti sendiri dan tes pemecahan masalah materi himpunan. Teknik pengumpulan data dalam penelitian ini dilakukan dengan memberikan tes, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa mayoritas siswa yang memiliki cara berpikir yang benar juga memiliki cara pemahaman yang benar. Dan mayoritas siswa yang memiliki cara berpikir yang salah juga memiliki cara pemahaman yang salah. Hasil penelitian juga menunjukkan bahwa sebagian besar kesalahan siswa disebabkan karena siswa kurang memahami soal dan konsep materi himpunan dengan baik.